2019
DOI: 10.1111/puar.13140
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Role of Top‐Down Supports in Horizontal Innovation Diffusion

Abstract: How do governments respond to multiple types of external pressures under limited resources? Are the effects of different types of diffusional pressures complementary or substitutive? This article approaches these questions by examining how top‐down supports modify the effects of horizontal pressures on local innovation adoption. Top‐down supports may complement or substitute the effects of horizontal pressures given the former's potential influence on perceived innovation advantage and visibility, organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 69 publications
0
17
0
1
Order By: Relevance
“…To investigate the institutional factors influencing shared SMT adoption, we utilize indicators of geographical proximity (see also Zhang and Zhu 2020). First, to capture coercive institutional pressures we calculate the distance from the headquarters of each district council to the offices of the Department for Communities and Local Government in London 4 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate the institutional factors influencing shared SMT adoption, we utilize indicators of geographical proximity (see also Zhang and Zhu 2020). First, to capture coercive institutional pressures we calculate the distance from the headquarters of each district council to the offices of the Department for Communities and Local Government in London 4 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the independent variables, we included measures of innovative culture/previous innovative practices, financial status, and leadership that are commonly applied in high‐quality public administration research (see Rho and Han 2020; Yi and Chen 2019; Zhang and Zhu 2020). First, to proxy for the potential influence of an innovative culture on the adoption of MI, we included an annual count of the companies operated by each district council, drawing on information in their annual accounts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This divergent role is particularly puzzling given that China as a politically centralised country has the capacity to coerce local governments, but also because centrally planned policy experiments have been attributed a great role in China's economic development (for example, Heilmann, 2008;Wang, 2009). Answering this question is theoretically significant because evidence has shown that the influence of higher-level governments takes precedence over other factors in authoritarian systems (Zhang and Zhu, 2020). Thus, analysing the variation of higherlevel government involvement in local innovation adoption can further advance the theoretical understanding of the vertical dimension of innovation theory.…”
Section: Introductionmentioning
confidence: 99%
“…This issue offers articles with topics that bridge policy and management questions. We begin with a set of three articles oriented around public policy, including a systematic review of the policy entrepreneurship literature (Frisch‐Aviram et al ), a comparative study of policy integration and administrative coordination reforms in 13 countries (Trein and Maggetti ), and an analysis of diffusional pressures from central to local governments in China (Zhang and Zhu ).…”
mentioning
confidence: 99%